Strategic Materials Positioning Matrix: An Application in the Automotive Industry in Southern Brazil - Saueressig, Gislaine Gabriele; Paris, Alaércio de; Bauer, Jéssica Mariella; Luchese, Juliane; Sellitto, Miguel Afonso; Valle Antunes Jr., José Antonio (International Journal of Industrial Engineering and Management, 2017)
The purpose of this article is to describe the application of the Strategic Materials Positioning Matrix (SMPM) in two families of items (bolts and plastic finishing) purchased by a focal company of the automotive industry in Southern Brazil. SMPM is a tool to manage the reception of materials required from suppliers in a supply chain. The research method was the case study. SMPM classifies materials according to their impact on the results and according to the risk of shortage involved in the supply process. SMPM organizes materials in four classes: non-critical, strategic, risk, and competitive materials. The main results of the analysis were a significant reduction in the number of shortages observed in the assembly line, and the number of storage facility units required for warehousing. The study details the actions that produced such results. Article history: Received (14.06.2016); Revised (12.12.2016); Accepted (24.03.2017)